Differences in body size and abundance of high Andean fishes, above and below the Neusa dam, Colombia - Olaya-Marin, Esther Julia (2022)
Introduction: Tropical rivers are increasingly being affected by fragmentation and regulation; and, in Colombia, dams are known to endanger endemic fishes through, among others, limited migration and reduced availability of sediment-based feeding networks. However, knowledge of native ichthyofauna affected by dams in high Andean rivers is still incipient. Objective: To assess the effects of the Neusa dam on the ichthyofauna. Methods: We compared two rivers’ sections, one above and one below the dam with the Richter IHA System, we sampled three 100 m long transects in each section, every two months, between 2017 and 2019. The fishes were returned to the river after body measurements. Results: We collected 729 individuals from five families; Trichomycterus bogotense were smaller under the dam; Oncorhynchus mykiss was smaller and less abundant; and there were no differences for Grundulus bogotensis and Eremophilus mutisii. Independently of climatic factors, O. mykiss and G. bogotensis were more abundant above the dam, and E. mutisii and T. bogotense under the dam. Conclusion: The five fish species differed in how the populations differed above and under the dam, suggesting that some are benefited by the dam, while others become smaller and less abundant.